Preparation and evaluation of cerium oxide-bovine hydroxyapatite composites for biomedical engineering applications - OKTAR, FAİK NÜZHET; GÜNDÜZ, OĞUZHAN (ELSEVIER SCIENCE BV, 2014)
The fabrication and characterization of bovine hydroxyapatite (BHA) and cerium oxide (CeO2) composites are presented. CeO2 (at varying concentrations 1, 5 and 10 wt%) were added to calcinated BHA powder. The resulting mixtures were shaped into green cylindrical samples by powder pressing (350 MPa) followed by sintering in air (1000-1300 degrees C for 4 h). Density, Vickers microhardness (HV), compression strength, scanning electron microscopy (SEM) and X-ray diffraction (XRD) studies were performed on the products. The sintering behavior, microstructural characteristics and mechanical properties were evaluated. Differences in the sintering temperature (for 1 wt% CeO2 composites) between 1200 and 1300 degrees C, show a 3.3% increase in the microhardness (564 and 582.75 HV, respectively). Composites prepared at 1300 degrees C demonstrate the greatest compression strength with comparable results for 5 and 10 wt% CeO2 content (106 and 107 MPa) which are significantly better than those for 1 wt% and those that do not include any CeO2 (90 and below 60 MPa, respectively). The results obtained suggest optimal parameters to be used in preparation of BHA and CeO2 composites, while also highlighting the potential of such materials in several biomedical engineering applications. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Sintering; Microstructure; Mechanical properties; Bovine hydroxyapatite; Cerium oxide; Bioceramics; MECHANICAL-PROPERTIES; BIOCOMPATIBILITY EVALUATION; LANTHANUM OXIDE; BONE; BHA; MICROSTRUCTURE; WHITLOCKITE; COATINGS; ZIRCONIA; TITANIUM